2006
DOI: 10.1111/j.1574-6968.2006.00177.x
|View full text |Cite
|
Sign up to set email alerts
|

The structure of the lipid anchor ofCampylobacter jejunipolysaccharide

Abstract: Campylobacter jejuni is a leading cause of gastroenteritis in humans. Campylobacter jejuni produces extracellular polysaccharides that have been characterized structurally and shown to be independent of lipopolysaccharides. Furthermore, it has been suggested that these C. jejuni polysaccharides are capsular in nature, although their lipid anchor has not been identified. In this report, the occurrence of a lipid-linked capsular-like polysaccharide in C. jejuni is conclusively shown, and the lipid anchor identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…This hypothesis is now complicated by the existence of the poly-Kdo linker. kpsC and kpsS mutants accumulate large aggregates of intracellular CPS (20,29), but there have been conflicting reports in the past as to whether the CPS is lipidated (18,31,33); here we provide evidence that these CPSs are not lipidated in E. coli. Notably, the intracellular aggregates from these mutants lack the characteristic membrane association seen in the aggregates of lipidated CPSs produced by export-deficient mutants (e.g., kpsT) (33).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…This hypothesis is now complicated by the existence of the poly-Kdo linker. kpsC and kpsS mutants accumulate large aggregates of intracellular CPS (20,29), but there have been conflicting reports in the past as to whether the CPS is lipidated (18,31,33); here we provide evidence that these CPSs are not lipidated in E. coli. Notably, the intracellular aggregates from these mutants lack the characteristic membrane association seen in the aggregates of lipidated CPSs produced by export-deficient mutants (e.g., kpsT) (33).…”
Section: Discussionmentioning
confidence: 53%
“…This lipid has been implicated in anchoring CPSs to the outer membrane (16). Mass spectrometry analysis of acid-hydrolyzed PSA from E. coli K1 and K92, as well as N. meningitidis group B, identified dipalmitoylglycerol as a component (17)(18)(19)(20). However, direct covalent linkage between the CPS and this lipid has not been established.…”
mentioning
confidence: 99%
“…Subsequently, genomic analysis provided confirmation that the observed PSs of C. jejuni were capsule (CPSs; Parkhill et al, 2000). Corcoran et al (2006) demonstrated the phospholipid anchor in three CPS types (HS3, HS6, and HS23/36) was dipalmitoyl-glycerophosphate, with ester-linked hexadecanoic acids. Campylobacter species, like other Gram negative mucosal pathogens and unlike other enteric pathogens, express a CPS and lipooligosaccharide (LOS; core → lipid A) in lieu of a full length LPS (O-chain → core → lipid A).…”
Section: Campylobacter Capsules: Structures and Geneticsmentioning
confidence: 99%
“…To solubilize released acylglycerols and diacylglycerols, the dried sample was extracted three times with 100 l of CHCl 3 /MeOH (1:1, v/v). This extract was then evaporated to dryness under a stream of nitrogen, and the components were peracetylated by treatment with 100 l of acetic anhydride, pyridine (1:1, v/v) at 86°C for 30 min (22). After cooling to room temperature, the reaction mixture was evaporated to dryness under a stream of nitrogen.…”
Section: Gas Chromatography/mass Spectrometry (Gc-ms) Analysis Of Fatmentioning
confidence: 99%